THU0679 Increased hospitalisation rates following heart failure diagnosis in rheumatoid arthritis. (12th June 2018) - Myasoedova, E.; Davis, J.M.; Achenbach, S.J.; Matteson, E.L.; Setoguchi, S.; Gabriel, S.E.; Crowson, C.S.
Abstract : Background: There is a 2-fold increased risk of heart failure (HF) in rheumatoid arthritis (RA) compared to the general population. Little is known about hospitalisation rates in patients with RA and HF. Objectives: We aimed to compare the frequency of and trends in hospitalizations after HF diagnosis in patients with and without RA during 1987–2015 and to assess risk factors for hospitalizations following HF in RA. Methods: The study included a retrospectively identified population-based cohort of patients with incident HF and prior RA (age ≥18 years, 1987 ACR criteria) and a cohort of incident HF patients without RA matched 3:1 on age, sex, and year of HF diagnosis. Hospitalizations at the time of HF diagnosis were excluded. All subjects were followed until death, migration, or 12/31/2015. Person-years methods and rate ratios (RR) from Poisson regression models were used to compare hospitalisation rates (number of hospitalizations divided by person-years of follow-up) between the groups. Conditional frailty models were used to examine risk factors for hospitalisation. Results: The study included 212 patients with RA (mean age at HF diagnosis 78.3 years; 68% female) and 636 non-RA patients (mean age at HF diagnosis 78.6 years; 68% female). The hospitalisation rate after HF diagnosis was higher in RA vs non-RA (RR 1.16; 95% CI 1.08–1.25). This difference may be decreasing after 2010 (figure 1). The magnitude of the increase was similar in both sexes and across all ages. In a subset with available echocardiography (n=68 RA and 449 non-RA), HF with preserved ejection fraction (HFpEF) was similarly prevalent in RA (57%) vs non-RA (51%; p=0.3). Among those with HF with reduced ejection fraction (HFrEF) RA patients had more hospitalizations than non-RA subjects (RR 1.65; 95% CI 1.29–2.09); this was not observed in HFpEF (RR 0.80; 95% CI 0.63–1.01). Following HF diagnosis, RA patients were more likely to be hospitalised for non-cardiovascular causes (RR 1.26; 95% CI 1.14–1.39), but not for HF (RR 0.96; 95% CI 0.76–1.21) or other cardiovascular causes (RR 0.99; 95% CI 0.81–1.20) compared to the non-RA patients. Readmission rates within 30 days of prior discharge were similar in RA and non-RA (p=0.14). Smoking (current or former), prior myocardial infarction (MI) and higher score on Charlson comorbidity index were associated with increased risk for hospitalisation: hazard ratio (HR) 1.33, 95% CI 1.06–1.68; HR 1.37, 95% CI 1.03–1.82; and HR 1.10, 95% CI 1.06–1.14, respectively. Conclusions: Hospitalisation rate following HF diagnosis was 16% higher in RA than in non-RA patients regardless of sex and age. This difference was particularly apparent between 1990 and 2010. Increased hospitalisation risk was mostly among patients with RA who had HFrEF rather than HFpEF, and was predominantly due to non-cardiovascular causes. Smoking, prior MI and Charlson comorbidity index were associated with increased risk of hospitalisation suggesting that increased complexity of management of patients with comorbid RA may play a role in more frequent hospitalizations in the RA cohort. Disclosure of Interest: None declared